Konsepsi Hadis dan Sunnah Prespektif Fazlur Rahman - habib habib bullah (LPPM Institut Pesantren KH. Abdul Chalim, 2018)
The emergence of world liberal Muslim thinkers today such as Fazlur Rahman (Pakistan) has become a discourse among observers of Islamic science. Fazlur Rahman is one of the neo-modernist intellectual figures. In terms of religion, he had experienced deep intellectual anxiety. According to him, Muslims have closed the doors of ijtihad, so what happened was extraordinary intellectual stagnation. In the end, Islam became a set of frozen doctrines and it is certainly difficult to appear in giving answers to the problems of the ummah amid the wave of modernity. For this reason, he takes different steps in expressing and formulating the concepts of sunnah and hadith, which is a response and form of criticism of the views of Muslims so far. One of the concepts offered by Fazlur Rahman is related to the hadith and sunnah. He considers that the hadith and sunnah need to be distinguished by a number of reasons stated. According to him the hadith is only a text that is raw or actually comes from the Prophet. Whereas the sunnah is the actualization or interpretation of the hadith text and must be adjusted to the historical setting when it comes to understanding a hadith. This shows that what is written in the hadith is not all said to be sunnah. However, not all sunnah are recorded in the hadith. Therefore, when hadith has been corrupted, since then, the sunnah has not developed. He is attached to the books scheduled. This research uses descriptive-analysis method which contains an analysis of the concept of fazlur rahman about the Sunnah hadith. This research produced a critical view of Fazlur Rahman about the concepts of hadith and sunnah.